Effect of Thyroxine Hormone Administration in Female Broodstock on Metamorphosis and Survival Rates of Marble Goby (Oxyeleotris marmorata, BLKR.) Larva - Hermawan, .; Junior, M. Zairin; Raswin, M.M. (Indonesian Society of Scientific Aquaculture (ISSA), 2004)
The experiment was conducted to study the effect of thyroxine hormone injection on female marble goby on metamorphosis and survival rate of their larva. Thyroxine hormone was injected into female at the dosage of 0,25 and 50 µg/g body weight. And then the female were reared with males in spawning tanks. Spawned eggs were hatched and the larva was observed for organogenesis, yolk absorption and growth in length. Formation of eye spot, swim bladder and body pigment becoming faster as the increase in thyroxine hormone dose. Yolk volume in larva that was obtained form thyroxine injected female decreased faster than those of control. Thyroxine hormone did not affected length growth and survival rate Key words: Marble goby, broodstock, thyroxine, metamorphosis, survival rate, larva